The Effect of Corporate Governance on the Performance of US Investment Banks. Issue 2 (May 2015) - Mamatzakis, Emmanuel; Bermpei, Theodora
Abstract : This paper focuses on the impact of the corporate governance, using a plethora of measures, on the performance of the US investment banks over the 2000–2012 period. This time period offers a unique set of information, related to the credit crunch, that we model using a dynamic panel threshold analysis to reveal new insights into the relationship between corporate governance and bank performance. Results show that the board size asserts a negative effect on performance consistent with the ' agency cost ' hypothesis, particularly for banks with board size higher than ten members. Threshold analysis reveals that in the post‐crisis period most of investment banks opt for boards with less than ten members, aiming to decrease agency conflicts that large boards suffer from. We also find a negative association between the operational complexity and performance. Moreover, the CEO power asserts a positive effect on performance consistent with the ' stewardship ' hypothesis. In addition, an increase in the bank ownership held by the board has a negative impact on performance for banks below a certain threshold. On the other hand, for banks with board ownership above the threshold value this effect turns positive, indicating an alignment between shareholders' and managers' incentives.